2020
DOI: 10.1016/j.remnie.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of COVID-19 pneumonia in asymptomatic patients after an oncological PET/CT

Abstract: Introduction On January 30, 2020, the World Health Organization (WHO) declared an international emergency due to the pandemic caused by a new coronavirus. There are some oncological indications that have special priority and studies are still being carried out despite the current situation. In these studies we have found suspicious findings of COVID-19 pneumonia in asymptomatic patients. The objective of this work is to assess the incidence of these findings, describe their characteristics and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…Incidental changes suggesting COVID-19 pneumonia in chest CT were founded in 4.1% of cancer patients derived to 18 F-FDG PET/CT in our centre, a lower proportion than previously reported (7,1-9.2%) (7,8,16). These heterogeneous results could be explained by the health care facilities and policies assumed in different medical centres and countries, the time-dependent transmissibility of the virus and/or other factors related with the study sample (4,11,17).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Incidental changes suggesting COVID-19 pneumonia in chest CT were founded in 4.1% of cancer patients derived to 18 F-FDG PET/CT in our centre, a lower proportion than previously reported (7,1-9.2%) (7,8,16). These heterogeneous results could be explained by the health care facilities and policies assumed in different medical centres and countries, the time-dependent transmissibility of the virus and/or other factors related with the study sample (4,11,17).…”
Section: Discussioncontrasting
confidence: 65%
“…Although the diagnostic potential of the metabolic activity observed in pulmonary infiltrates of suggestive or confirmed COVID-19 pneumonia on PET/CT studies has been described in some recent researches, the correlation between tomographic structural changes (CO-RADS system) and metabolic activity (SUVmax) of the lung parenchyma had not been evaluated in detail until now (6)(7)(8)(9)(10)(16)(17)(18)(19)(20)(21). Our preliminary results could provide a new perspective on the pathophysiology of SARS2-CoV-2 lung infection and even redefine the best diagnostic imaging criteria in several patient subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study of 160 adult patients, we observed a total prevalence of incidental findings of 16.25% of which 9.3% were lung-related compatible with COVID-19 pulmonary manifestations and 7% with other incidental findings such as PE, abnormal cardiac uptake, increased FDG uptake in the parotid glands and the tonsils and signs of increased upper gastrointestinal uptake and colitis known extrapulmonary organs affected by COVID-19 on imaging [11]. The published literature on the role of 18F-FDG PET/CT value during the COVID-19 pandemic is scarce and consists mainly of sporadic case reports and a larger series of 65 asymptomatic patients from Italy and 129 from Spain, which showed incidental pulmonary findings in six (9%) and eleven (8.5%) of patients compatible with COVID-19 respectively [15,16]. Although extrathoracic symptoms have been described [4], there are no comprehensive publications for COVID-19-related extrathoracic imaging findings on 18F-FDG PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…The true prevalence of COVID-19 pneumonia in asymptomatic cancer patients referred to PET/CT is unknown. Only available data are derived from a few small case series of subjects with suspicious tomographic findings and none/partial laboratory confirmation [4] , [5] , [6] , reporting a frequency of tomographic suggestive findings ranging broadly from 8.5% [5] to 39% [6] , and confirmed COVID-19 pneumonia in 4% and 8% of studies, respectively.…”
Section: Discussionmentioning
confidence: 99%